Characterization of QTL and Environmental Interactions Controlling Flowering Time in Andean Common Bean (Phaseolus vulgaris L.) - González, Ana M.; Yuste-Lisbona, Fernando J.; Weller, Jim; Vander Schoor, Jacqueline K.; Lozano, Rafael; Santalla, Marta (Frontiers in Plant Science, 2021)
Genetic variation for response to flowering time plays an important role in adaptation to environments with different photoperiods, and as consequence is an important contributor to plant productivity and yield. To elucidate the genetic control of flowering time (days to flowering, DTF; growing degree days, GDD) in common bean, a facultative short-day plant, a quantitative trait loci (QTL) analysis was performed in a recombinant inbred (RI) mapping population derived from a cultivated accession and a photoperiod sensitive landrace, grown in different long-day (LD) and short-day (SD) environments by using a multiple-QTL model approach. A total of 37 single-locus QTL across 17 chromosome regions and 36 gene-by-gene interactions for time to flowering and response to photoperiod were identified. The DTF QTL accounted for 28% and 11% on average of the phenotypic variation in the population across LD and SD environments, respectively. Of these, a genomic region on chromosome 4 harboring the major DTF QTL was associated with both flowering time in LD and photoperiod response, controlling more than 60% of phenotypic variance, whereas a major QTL on chromosome 9 explained up to 32% of flowering time phenotypic variation in SD. Different epistatic interactions were found in LD and SD environments, and the presence of significant QTL × environment (QE) and epistasis × environment interactions implies that flowering time control may rely on different genes and genetic pathways under inductive and non-inductive conditions. Here, we report the identification of a novel major locus sensitive to daylength on chromosome 4, which may be a core locus interacting with other loci for controlling common bean flowering time and photoperiod response. Our results have also demonstrated the importance of these interactions for flowering time control in common bean, and the potential underlying complexity of flowering time pathways. This knowledge will help to identify and develop opportunities for adaptation and breeding of this legume crop.